Borneo studies: perspectives from a jobbing social scientist. - Victor T. King, (Universiti Kebangsaan Malaysia, 2009)
The paper comprises an intellectual journey through Borneo. But rather than summarising the results of his and others research on Borneo’s societies, cultures and histories and demonstrating their contribution to knowledge within certain fields of scholarship and theoretical tradition the author dwells on a particular style of research which he refers to as ‘jobbing’. Popular reactions to the use of such a concept usually turn on the images which it conjures of an unprofessional and unscholarly approach to what are serious matters of academic endeavour. However, in arguing that much of his own research can be characterised as ‘jobbing’, that it falls somewhere in the middle of a continuum from theory to practice drawing on concepts in an eclectic and pragmatic way in order to analyse and present materials gathered from a diverse range of sources in a logical and meaningful explanatory narrative, the author proposes that much of the research undertaken in Borneo over the last half century can also be categorised in the same fashion. The paper ranges over ‘jobbing concepts’, the relations between area studies and a jobbing lifestyle, the apprenticeship of a jobbing researcher, the ways in which research both on the ‘Maloh’ of interior Kalimantan and on Borneo more generally can be appreciated from this perspective, and the problems posed by globalisation approaches for those whose work is rooted in the understanding of ‘on-the-ground’ structures and processes.